Fatty acid profile driven by maternal diet is associated with the composition of human milk microbiota - Marsh, Alan J.; Azcarate-Peril, M. Andrea; Aljumaah, Mashael R.; Neville, Jessica; Perrin, Maryanne T.; Dean, Lisa L.; Wheeler, Michael D.; Hines, Ian N.; Pawlak, Roman (Frontiers in Microbiomes, 2022)
Little is known regarding the impact of diet on breast milk microbiome. We hypothesized that vegan, vegetarian, and omnivore diets would impact the human milk microbiome. We also aimed to explore associations between human milk fatty acid concentrations and microbial composition. A cross-sectional microbiome diversity analysis of human milk samples (N = 72) was performed using 16S rRNA amplicon sequencing. Human milk microbial diversity was not associated with diet type. However, analysis of microbiome in relation to fatty acid profiles revealed significant differences in the overall composition of the human milk microbiota between high (> 0.7% of total fat) and low (< 0.7%) trans-fatty acid groups (TF) (p = 0.039, pairwise PERMANOVA p = 0.035), high (> 40%) versus low (< 40%) saturated fatty acids (UniFrac p = 0.083, PERMANOVA p = 0.094), and high (>60%) versus low (<60%) unsaturated fatty acids (UF) (UniFrac p = 0.094, PERMANOVA p = 0.093). 84% of samples from omnivore mothers were in the high TF group compared to only 12% of samples from vegans. Gut-associated species (Faecalibacterium, Blautia, Roseburia and Subdoligranulum) and Lactobacillus, were characteristic of both high UF and TF groups, but not the low-fat groups. Functional analysis revealed 2,4-dichlorophenol 6-monooxygenase was differentially abundant in the high UF group. Although microbiome diversity did not differ by diet type, considering differences in TF breast milk content differed by diet group, the findings highlight the relationship between maternal diet and the microbial profile of human milk.